1985
DOI: 10.1070/sm1985v052n02abeh002901
|View full text |Cite
|
Sign up to set email alerts
|

ON INFINITE $ p$-GROUPS WITH CYCLIC SUBGROUPS

Abstract: The Giotto magnetometer experiment employs a lowmass (1.357 kg), low-power (818 mW) instrument in a dual magnetometer configuration using flux gate sensors of the ring core type. It has provided accurate vector magnetic field measurements on its way to and near comet Halley, working flawlessly from switch-on on 22 August 1985 to the formal end of the mission on 15 March 1986.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In [32] the second author of the present article proved that there exists a continuum of 2-generated non-isomorphic groups with the property that every proper subgroup is cyclic of prime order. In [10] G. Deryabina showed that for every odd prime p there is continuum of non-isomorphic simple groups, generated by two elements, such that all their proper subgroups are cyclic p-groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [32] the second author of the present article proved that there exists a continuum of 2-generated non-isomorphic groups with the property that every proper subgroup is cyclic of prime order. In [10] G. Deryabina showed that for every odd prime p there is continuum of non-isomorphic simple groups, generated by two elements, such that all their proper subgroups are cyclic p-groups.…”
Section: Introductionmentioning
confidence: 99%
“…In [10] G. Deryabina showed that for every odd prime p there is continuum of non-isomorphic simple groups, generated by two elements, such that all their proper subgroups are cyclic p-groups.…”
Section: Remarkmentioning
confidence: 99%
“…In [3] it was proved that for every odd prime p there exists an infinite simple group whose proper subgroups are cyclic p-groups. Moreover, it was shown that for every odd prime p there exist continuum many nonisomorphic such groups with isomorphic subgroup lattices.…”
Section: Direct Product Of Coprime Groups Given In (I) and (Ii)mentioning
confidence: 99%